2012
DOI: 10.3109/17453674.2012.693016
|View full text |Cite
|
Sign up to set email alerts
|

Hip resurfacing arthroplasty: short-term survivorship of 4,401 hips from the Finnish Arthroplasty Register

Abstract: Background and purposePopulation-based registry data from the Nordic Arthroplasty Register Association (NARA) and from the National Joint Register of England and Wales have revealed that the outcome after hip resurfacing arthroplasty (HRA) is inferior to that of conventional total hip arthroplasty (THA). We analyzed the short-term survival of 4,401 HRAs in the Finnish Arthroplasty Register.MethodsWe compared the revision risk of the 4,401 HRAs from the Register to that of 48,409 THAs performed during the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Furthermore, only one previous study focused specifically on the ASR TM prosthesis, which is known to have a lower survival rate than other MoM devices [29]. This is likely attributable to the specific design differences between the ASR TM and similar hip resurfacing devices.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, only one previous study focused specifically on the ASR TM prosthesis, which is known to have a lower survival rate than other MoM devices [29]. This is likely attributable to the specific design differences between the ASR TM and similar hip resurfacing devices.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that 29% to 34% of hip resurfacing arthroplasties have been performed in females [6,29,31]. Some studies have indicated that females receiving hip resurfacing arthroplasties with MoM prostheses are at an especially high risk of revision surgery and report higher levels of pain compared with males [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Implants such as the ASR system (DePuy Orthopaedics, Johnson & Johnson, Warsaw, IN, USA) experienced high failure rates and were recalled from the market. [25][26][27][28] The same concerns were extended to all metal on metal bearing hip replacements/resurfacings and in 2012 The Medicines and Healthcare Products Regulatory Agency (MHRA) (UK) issued guidelines to assess the performance and safety of these implants.…”
mentioning
confidence: 99%
“…The short-term survival of the BHR resurfacing in Finland is worse than in Australia and in England and Wales. Despite this, the BHR has been one of the best performing resurfacing designs in Finland (20).…”
Section: Discussionmentioning
confidence: 99%